2008
DOI: 10.1021/bc8001826
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Entry and Nuclear Targeting By a Highly Anionic Molecular Umbrella

Abstract: A fluorescently-labeled, persulfated molecular umbrella (1) has been synthesized from cholic acid, lysine, spermine and Coumarin 343 and found capable of entering live HeLa cells. The distribution of 1 throughout the cytoplasm and the nucleus was diffuse and punctate, respectively. This finding, together with its ability to cross liposomal membranes by passive diffusion, suggests that passive diffusion plays a significant role in the ability of 1 to enter cells. The fact that 1 is concentrated at the nucleus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 11 publications
1
22
0
1
Order By: Relevance
“…S11 ). It should be noted that, although the CDs were not modified with any nucleus-targeted signals or chemicals, the CDs were successfully internalized into the cells as well as the nucleus which is attributed to the zwitterionic surface state and small size of CDs 22 23 24 25 26 27 28 29 30 31 32 33 34 35 . The positively charged surface group on the CDs can effectively interact with the negatively charged cell membranes to enter the cytoplasm 23 via clathrin- and caveolae-mediated pathway along with the involvement of passive diffusion 24 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S11 ). It should be noted that, although the CDs were not modified with any nucleus-targeted signals or chemicals, the CDs were successfully internalized into the cells as well as the nucleus which is attributed to the zwitterionic surface state and small size of CDs 22 23 24 25 26 27 28 29 30 31 32 33 34 35 . The positively charged surface group on the CDs can effectively interact with the negatively charged cell membranes to enter the cytoplasm 23 via clathrin- and caveolae-mediated pathway along with the involvement of passive diffusion 24 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Cytoplasmic and nuclear uptake of nanoparticle cargo in live cells can be determined by the size 22 and surface charge 23 24 25 26 27 28 29 . In addition, positively charged nanoparticles are preferentially internalized by cells and negatively charged ones interact with nuclei whose pH is consistently 0.3 to 0.5 units above that of the cytosol 23 24 25 26 27 28 29 . Based on this observation, it is expected that the preparation of zwitterionic CDs with both positively and negatively charged functional groups, can facilitate cytoplasmic uptake and subsequent nuclear translocation of theranostic drug-vehicle conjugates.…”
mentioning
confidence: 99%
“…To address this question, we synthesized a fluorescently-labeled molecular umbrella analog of 18 (i.e., 19 ) and investigated its interaction with live HeLa cells (Figure 23) (35). …”
Section: Cellular Uptake Of Molecular Umbrellasmentioning
confidence: 99%
“…Specifically, we showed that a bioconjugate derived from one spermine, four lysine and eight cholic acid groups, having all of its hydroxyl groups sulfated (i.e., 1 ), exhibits significant anti-HIV and anti-HSV activity (Figure 1) (5,6). In a related investigation, we showed that a fluorescently-labelled analog of 1 readily enters live HeLa cells, and provided evidence that passive transport may be playing a significant role in this internalization process (7). …”
mentioning
confidence: 90%